2021
DOI: 10.3389/fonc.2021.651809
|View full text |Cite
|
Sign up to set email alerts
|

An Immune Model to Predict Prognosis of Breast Cancer Patients Receiving Neoadjuvant Chemotherapy Based on Support Vector Machine

Abstract: Tumor microenvironment has been increasingly proved to be crucial during the development of breast cancer. The theory about the conversion of cold and hot tumor attracted the attention to the influences of traditional therapeutic strategies on immune system. Various genetic models have been constructed, although the relation between immune system and local microenvironment still remains unclear. In this study, we tested and collected the immune index of 262 breast cancer patients before and after neoadjuvant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…However, tissue biopsy during NAC is challenging, and circulating immune cells have been extensively evaluated during NAC. Previous studies have indicated that these circulating cells may also be informative and capable of serving as promising biomarkers to predict treatment response ( 59 61 ). A study quantifying myeloid-derived suppressor cells (MDSCs) and Tregs by flow cytometry in blood samples from 34 pre-NAC TNBC patients has revealed a negative correlation between early MDSC (eMDSC) levels and NAC response ( 61 ).…”
Section: Cytometrymentioning
confidence: 99%
“…However, tissue biopsy during NAC is challenging, and circulating immune cells have been extensively evaluated during NAC. Previous studies have indicated that these circulating cells may also be informative and capable of serving as promising biomarkers to predict treatment response ( 59 61 ). A study quantifying myeloid-derived suppressor cells (MDSCs) and Tregs by flow cytometry in blood samples from 34 pre-NAC TNBC patients has revealed a negative correlation between early MDSC (eMDSC) levels and NAC response ( 61 ).…”
Section: Cytometrymentioning
confidence: 99%
“…The following post-NAT/pre-NAT immune indicator values were related to the long-term prognosis of patients: CD4 + :CD8 + T cell ratio; CD3 + CD8 + T cell percentage; CD16 + CD56 + natural killer (NK) cell absolute value (Abs); CD3 + CD4 + helper T cell percentage; and summation of T, B, and NK cell percentages [lymphosum (T+B+NK)]. We then used the support vector machine (SVM) to train the prediction model 9 . In this study we focused on the efficacy of NAT and optimized the prediction model using machine learning (ML).…”
Section: Introductionmentioning
confidence: 99%
“…However, traditional biostatistical methods (e.g., logistic regression or linear regression) could not provide higher precision in health-data prediction, especially in real-world research. Support vector machine (SVM) is widely used as a type of supervised learning algorithm which analyzes data and recognizes patterns, mainly used for binary classification and regression by linear or nonlinear decision boundary [21]. It aims to divide samples into worthy bifurcations that enable the prediction of labels from one or more feature vectors.…”
Section: Introductionmentioning
confidence: 99%